Analysis of Revenue, Marketing Costs, and Profit Before and During the Covid-19 Pandemic - Lisdawati Lisdawati; Susanto Yogo Purnomo; Melinda Melinda; Hofandrik Lase; Eka Yulianto; Yusnina Yusnina (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The impact of the Covid-19 pandemic has made many business sectors experience difficult times, both in small, medium and large industries, so this study aims to find out and analyze whether there were differences in income, marketing costs and profits before and during the COVID-19 pandemic. The method used is descriptive quantitative. The sample in this study were 50 MSME respondents in Pulo Gadung. Testing the data using descriptive statistics with normality test, paired sample t test, Wilcoxon marked ranking test. The results of the first study showed that there was no difference in income before and during the covid-19 pandemic.